2018
DOI: 10.18520/cs/v114/i03/679-685
|View full text |Cite
|
Sign up to set email alerts
|

Differential Bleaching Patterns in Corals of Palk Bay and the Gulf of Mannar

Abstract: The status of reefs in Palk Bay and the Gulf of Mannar was studied during April-May 2016 following a bleach alert, as the sea surface temperature recorded a sudden increase from 30.5C to 34.0C in Gulf of Mannar. About 71.48%  8.9% of the corals in Palk Bay and 46.04%  3.78% in Thoothukkudi group of Islands in Gulf of Mannar were found bleached, showing a clearly decreasing trend from north to south, which could be attributed to the corresponding pattern in intensity of SST recorded in the study sites. Obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 15 publications
0
10
0
2
Order By: Relevance
“…However, a similar result was found in the present study, where the Tuticorin group of Islands represents a high number of bleached corals than other areas of GoM, followed by PB (Figure 5). Earlier studies documented that branching corals were more tolerant to increased SST than massive corals, which is a sign of prolonging adaptive bleaching patterns found in GoM (Krishnan et al 2018;Ramesh et al 2020). In the current study, species-specific evaluation of bleaching revealed the same pattern of bleaching in which massive corals such as P. lutea, P. solida, D. favus, D. speciosa, F. halicora are bleached intensively, whereas, bleaching among branching corals limited mainly to A. muricata, A. hyacinthus, and M. digitata.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…However, a similar result was found in the present study, where the Tuticorin group of Islands represents a high number of bleached corals than other areas of GoM, followed by PB (Figure 5). Earlier studies documented that branching corals were more tolerant to increased SST than massive corals, which is a sign of prolonging adaptive bleaching patterns found in GoM (Krishnan et al 2018;Ramesh et al 2020). In the current study, species-specific evaluation of bleaching revealed the same pattern of bleaching in which massive corals such as P. lutea, P. solida, D. favus, D. speciosa, F. halicora are bleached intensively, whereas, bleaching among branching corals limited mainly to A. muricata, A. hyacinthus, and M. digitata.…”
Section: Discussionmentioning
confidence: 93%
“…This study documented some important reef health details of the coral communities, the relative abundance of coral species, the bleaching status of corals, and threats to the reefs that exist in GoM and PB. Coral reefs are fragile and highly virulent to natural and anthropogenic disturbances, including climate change, sedimentation, destructive fishing, shoreline operations, and tangling ghost nets (Krishnan et al 2018). Therefore, community structure is highly variant through time; hence, the percentage of live coral coverage also significantly varied compared to the earlier data of 2001 and 2015 (Shanmugaraj et al 2013;ENVIS 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, reports of turf algae being a dominant component in the atolls 17 might indicate towards a faster transition. Globally Elevated SST is a major threat to coral reefs 19 , and the reefs of India 20,21,22 including the atolls 23 are no different. With reports indicating that elevated SST has already depleted the coral ecosystem of Lakshadweep which was evident during 1998 17 , 2010 23 and 2016 19 mass bleaching events, it can provide an opportunity for sponges to invade 24 .…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, reports of turf algae being a dominant component in the atolls (Arthur et al 2005) might indicate a faster transition. Globally Elevated SST is a major threat to coral reefs (Hughes et al 2018), and the reefs of India (Edward et al 2018;Krishnan et al 2018;Raj et al 2018b) including the atolls (Vinoth et al 2012) are no different. With reports indicating that elevated SST has already depleted the coral ecosystem of Lakshadweep, which was evident during 1998 (Arthur et al 2005), 2010 (Vinoth et al 2012), and 2016 (Hughes et al 2018) mass bleaching events, it can provide an opportunity for sponges to invade (Bell et al 2013) .…”
Section: J Ttmentioning
confidence: 99%